Reliability of the Lactate Scout point-of-care instrument for the determination of blood L-lactate concentration in sheep - Kaynar, Ozgur; Karapinar, Tolga; Hayirli, Armagan; Baydar, Ersoy (Wiley-Blackwell, 2015)
Background: Data on accuracy and precision of the Lactate Scout point-of-care (POC) analyzer in ovine medicine are lacking. Objective: The purpose of the study was to assess the reliability of the Lactate Scout in sheep. Materials and Methods: Fifty-seven sheep at varying ages with various diseases were included. Blood lactate concentration in samples collected from the jugular vein was measured immediately on the Lactate Scout. Plasma L-lactate concentration was measured by the Cobas autoanalyzer as the reference method. Data were subjected to Student's t-test, Passing-Bablok regression, and Bland-Altman plot analyses for comparison and assessment of accuracy, precision, and reliability. Results: Plasma L-lactate concentration was consistently lower than blood L-lactate concentration (3.06 +/- 0.24 vs 3.3 +/- 0.3 mmol/L, P < .0001). There was a positive correlation between plasma and blood L-lactate concentrations (r = .98, P < .0001). The Lactate Scout had 99% accuracy and 98% precision with the reference method. Blood (Y) and plasma (X) L-lactate concentrations were fitted to Y = 0.28 + 1.00 . X, with a residual standard deviation of 0.31 and a negligible deviation from the identity line (P = .93). The bias was fitted to Y = 0.10 + 0.05 . X, with Sy.x of 0.44 (P < .07). Conclusions: The Lactate Scout has high accuracy and precision, with a negligible bias. It is a reliable POC analyzer to assess L-lactate concentration in ovine medicine.
Keywords: Accuracy; bias; lactate meter; precision; ovine medicine